Modification of CTAB incubation time in the isolation of DNA from Staphylococcus aureus - Awaliyah, Arisma Putri; Prayekti, Endah (Journal of Indonesian Medical Laboratory and Science, 2024)
Background: DNA was an essential component in organisms that regulates biological activity. DNA analysis began with isolating pure, highly concentrated DNA, often used the CTAB method to isolate DNA from bacteria. DNA quality affected by incubation timed and temperature as well as its purity. The right incubation timed could optimize the degradation of proteins in the cell wall and maximize the released of DNA from the cell. DNA purity is good if the 260/280 absorbance ratio valued is 1.8-2.0. Objectives: This studied aimed to obtained the highest concentration and quality of DNA by modifying the incubation time of CTAB used Staphylococcus aureus DNA. Materials and Methods: This studied uses quantitative methods with the typed in experimental researched. The isolation stage included cell lysis with CTAB buffer and proteinase-K, purification stage with chloroform: isoamyl alcohol (24:1), DNA precipitation stage with isopropanol. Results: The average result of DNA purity obtained from the incubation treatment for 10 minutes was 1.89, for 20 minutes incubation was 1.46, and for 30 minutes incubation was 1.23. The average DNA concentration obtained from the incubation treatment for 10 minutes was 153 ng/µL, for 20 minutes incubation was 78.2 ng/µL, and for 30 minutes incubation was 26 ng/µL. Electrophoresis results at 10 minutes incubation time clearly visible DNA bands, 20 minutes incubation time DNA bands looked faint, and 30 minutes incubation time is not visible DNA bands. Conclusions: Based on the results of the studied, modification of CTAB incubation time with an incubation time of 10 minutes is the result of the highest concentration and quality of DNA using Staphylococcus aureus DNA.